An MILP Model for the Analysis of Operation of Energy Storage Devices in Distribution Systems - Macedo, Leonardo H. [UNESP]; Franco, John F. [UNESP]; Romero, Ruben [UNESP]; Rider, Marcos J.; IEEE (Ieee, 2016)
This paper presents a mixed-integer linear programming model to define the optimal operation of energy storage devices in radial distribution systems. The objective considered is the reduction of the energy purchase cost from the distribution substation. The modeling of the energy storage devices determines both the charging and discharging periods, and the injected and extracted power. In addition, the number of daily charge/discharge cycles of the storage devices is limited to avoid an excessive reduction of their lifespan. The proposed model was used to analyze the influence of the location of energy storage devices in the operation of a system. The efficiency of the methodology was tested in several cases, using a 136-node distribution system.
Keywords: Energy storage devices; mixed-integer linear programming; operation of distribution systems